THE EFFECTIVENESS OF THE GEMAR KARIPAN PROGRAM AS A PREVENTIVE EFFORT TO REDUCE THE PREVALENCE OF STUNTING INCIDENCE RATES: Heri Triwibowo, , Heni Frilasari, M.Sajidin, Rina Mardiyana Universitas Bina Sehat PPNI Mojokerto Email: herippni@gmail.com - triwibowo, heri; Frilasari, Heni; Sajidin, M; Mardiyana, Rina (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Stunting is a form of stunted child growth. Until now, stunting is a nutritional problem that needs attention). The incidence of stunting in Indonesia in 2013 was 37.2% (Riskesdas, 2013) and in 2018 it decreased to 30.8% (Health, 2018). One indicator of growth in children is height. Inadequate nutritional intake in infants and children will greatly affect the growth and development of the child's body and brain (Kusmini et al., 2020) Efforts that can be given to the problems mentioned above include providing assistance to families of toddlers so that the prevalence of stunting can be prevented. This study aims to prove that the Gemar Karipan Program is effective in reducing the prevalence of stunting. The stages and methods of this study used a quasi-experimental research design with a control group. The Sampling technique uses Total Sampling of as many as 27 respondents. Researchers provide research stages starting from data collection through examining growth in the treatment group and the control group. The treatment group was given a midwifery intervention using the GEMAR KARIPAN method which was carried out by visiting the respondent's house, while the control group was given an examination according to the procedure when they arrived at the posyandu. Furthermore, data analysis was carried out and conclusions were drawn about the effectiveness of the GEMAR KARIPAN method in reducing the prevalence of stunting.